Failure mechanism and control of coal bursts triggered by mining induced seismicity in steeply inclined and extra thick coal seam - Cao, Jinrong; Dou, Linming; He, Jiang; Zhu, Guangan; Wang, Zhengyi; Bai, Jinzheng; Han, Zepeng (Frontiers in Earth Science, 2023)
With the increase in mining depth, coal bursts have become a major challenge in the safe mining of steeply inclined and extra thick coal seams (SIETCSs). Based on a typical mining induced seismicity triggered coal burst (MSTCB) in SIETCS, a large-scale numerical model was developed using the Universal Distinct Element Code. The numerical model was calibrated and validated by laboratory results and field observations. The stress evolution, crack development and ejection velocity patterns in the MSTCB were analysed, and the effect of mining induced seismicity vibration velocity on the MSTCB was discussed. The results show that a triangular static stress concentration zone is formed in the coal on the roof side. And the high-energy mining induced seismicity leads to high dynamic stresses in the coal at the roof side rib and top of the headentry. Coal bursts occur under the superposition of static and dynamic stresses. The MSTCB results in tensile failure near the headentry surface and shear failure in the depth. The vibration velocity has a significant effect on the roof side rib and top of the headentry, while it has only a slight effect on the working face rib and bottom of the headentry. The dynamic stress and ejection velocity in the roof side rib and top of the headentry are positively correlated with the vibration velocity. Finally, measures for MSTCB prevention were proposed. The findings presented in this study can provide guidance for the prevention and control of MSTCBs in SIETCSs.